2018
DOI: 10.1002/ccd.27794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non‐compliant balloon postdilatation on magnesium‐based bioresorbable vascular scaffolds

Abstract: NC balloon postdilatation of Magmaris® BRS is required to achieve optimal expansion. It significantly reduces malapposition and can safely be performed without relevant rates of strut fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In ex vivo porcine carotid jugular arteriovenous shunt models, magnesium-based scaffolds have shown reduced thrombogenicity compared to the Absorb scaffold and to a stainless steel stent, suggesting that the magnesium-based metal scaffold may have inherent properties that reduce thrombogenicity 4,5 . No scaffold thrombosis has been reported for the second-generation drug-eluting absorbable magnesium scaffold (DREAMS 2G, commercial name Magmaris ® ; Biotronik AG, Bülach, Switzerland) in 184 patients studied up to 24 months, which is beyond its degradation time of approximately 12 months [6][7][8] . We now report three-year outcomes of BIOSOLVE-II (BIOTRONIK -Safety and Clinical PerFormance of the Drug Eluting Absorbable Metal Scaffold in the Treatment of Subjects with de NOvo Lesions in NatiVE Coronary Arteries) to assess vessel response up to two years post resorption.…”
Section: Introductionmentioning
confidence: 99%
“…In ex vivo porcine carotid jugular arteriovenous shunt models, magnesium-based scaffolds have shown reduced thrombogenicity compared to the Absorb scaffold and to a stainless steel stent, suggesting that the magnesium-based metal scaffold may have inherent properties that reduce thrombogenicity 4,5 . No scaffold thrombosis has been reported for the second-generation drug-eluting absorbable magnesium scaffold (DREAMS 2G, commercial name Magmaris ® ; Biotronik AG, Bülach, Switzerland) in 184 patients studied up to 24 months, which is beyond its degradation time of approximately 12 months [6][7][8] . We now report three-year outcomes of BIOSOLVE-II (BIOTRONIK -Safety and Clinical PerFormance of the Drug Eluting Absorbable Metal Scaffold in the Treatment of Subjects with de NOvo Lesions in NatiVE Coronary Arteries) to assess vessel response up to two years post resorption.…”
Section: Introductionmentioning
confidence: 99%
“…The mean post-dilation balloon diameter was 3.4 ± 0.3 mm, inflated at a mean pressure of 18.5 ± 2.4 atm. This reflected the adherence of the operators to the predefined Mg-BVS implantation technique recommendations [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The POSTDIL-STEM trial also found that post-dilatation during primary PCI for ST-elevation MI enhanced the stent expansion, apposition, and post-PCI fractional flow reserve without having a significant impact on the coronary microcirculation [ 19 ]. Furthermore, post-dilatation with an NC balloon is necessary to achieve optimal expansion while effectively minimizing malposition [ 20 ].…”
Section: Discussionmentioning
confidence: 99%